Enhanced gated-diode-triggered silicon-controlled rectifier for robust electrostatic discharge (ESD) protection applications*Project supported by the National Natural Science Foundation of China (Grant Nos. 61874098 and 61974017) and the Fundamental Research Project for Central Universities, China (Grant No. ZYGX2018J025). (October 2020) - Song 宋, Wenqiang 文强; Hou 侯, Fei 飞; Du 杜, Feibo 飞波; Liu 刘, Zhiwei 志伟; Liou 刘, Juin J. 俊杰
Abstract : A robust electron device called the enhanced gated-diode-triggered silicon-controlled rectifier (EGDTSCR) for electrostatic discharge (ESD) protection applications has been proposed and implemented in a 0.18-μm 5-V/24-V BCD process. The proposed EGDTSCR is constructed by adding two gated diodes into a conventional ESD device called the modified lateral silicon-controlled rectifier (MLSCR). With the shunting effect of the surface gated diode path, the proposed EGDTSCR, with a width of 50 μm, exhibits a higher failure current ( i.e., 3.82 A) as well as a higher holding voltage ( i.e., 10.21 V) than the MLSCR.